PREPARING STUDENTS TO USE VIRTUAL TRAVEL TO DEVELOP PRESCHOOLERS' COGNITIVE INTEREST (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The modern educational space is undergoing significant changes under the influence of digital technologies, which open up new opportunities for teaching and upbringing of children. One of the innovative means of developing the cognitive interest of preschool children is the use of virtual journeys, which allow to broaden the worldview, stimulate curiosity and intensify educational and cognitive activities. The article deals with theoretical and practical aspects of preparing students for the use of virtual travel. The importance of digital technologies in preschool education, their impact on the formation of curiosity and motivation to learn about the world around us is analysed. The key methodological aspects of preparing future teachers for the implementation of virtual excursions, including the choice of content, integration with the educational programme and creation of an interactive educational environment are outlined. Attention is focused on the importance of developing students' digital competence for the effective use of modern educational resources in working with preschool children. An experimental study was conducted, the respondents of which were 67 2nd year students of the bachelor's degree in speciality 012 Preschool Education of Vinnytsia Mykhailo Kotsiubynskyi State Pedagogical University, studying under the educational programmes “Preschool Education. Primary Education”, “Preschool Education. Speech Therapy” full-time and part-time study programmes. The readiness of future specialists to use virtual travel to develop the cognitive interest of preschoolers is investigated. For this purpose, the relevant criteria were developed and their indicators were determined: motivational (need to use virtual travel; desire for new knowledge in this area); cognitive (knowledge of the peculiarities of using virtual travel to develop the cognitive interest of preschool children); activity (ability to use virtual travel in the educational process). The study revealed mostly medium and low levels of readiness of the students who participated in the survey. The authors of the article provide examples of technologies that should be used in working with students to increase their readiness to use virtual travel in teaching preschoolers: Google Earth and Google Maps – for virtual tours of the world, CoSpaces Edu – for creating interactive media content (virtual reality, augmented reality, interactive 3D content), BYOD technology (“bring your own device”) – promotes the integration of mobile learning with other competence-based technologies. The recommendation to reduce the number of applicants with adequate and initial levels of readiness to use virtual travel in the development of cognitive interest of preschool children is to study the relevant elective discipline.